Quantification of soft-tissue vibrations in running: Accelerometry versus high-speed motion capture - Coza, A.; Nigg, B. N.; Fliri, L. (Journal of Applied Biomechanics, 2010)
Soft-tissue vibrations can be used to quantify selected properties of human tissue and their response to impact. Vibrations are typically quantified using high-speed motion capture or accelerometry. The aim of this study was to compare the amplitude and frequency of soft-tissue vibrations during running when quantified by high-speed motion capture and accelerometry simultaneously. This study showed: (a) The estimated measurement errors for amplitude and frequency were of the same order of magnitude for both techniques. (b) There were no significant differences in the mean peak frequencies and peak amplitudes measured by the two methods. (c) The video method showed an inability to capture high frequency information. This study has shown that a tradeoff has to be made between the accuracy in amplitude and frequency when these methods are employed to quantify soft tissue vibrations in running.